Managerial Fears and Hopes: The Human Side of Algorithmic Management in Organisations - Kamasak, Rıfat; Palalar Alkan, Deniz; Sungur, Mehmet Zihni; Kılıç, Şeyda Betül (Emerald Publishing Limited, 2025)
Implementation of algorithmic systems that can optimise decision-making processes and enhance operational efficiency and agility is contingent upon managers’ beliefs about their value and practicality. Drawing on the technology acceptance model, the authors explore 23 middle and top managers’ perceptions of algorithmic management’s potential benefits and usefulness, along with ethical and psychological concerns. While managers generally found algorithmic management beneficial in efficiency, quick decision-making, innovation and continuous learning, they expressed their ethical concerns as transparency, fairness and employee well-being. They also mentioned algorithmic management as an opportunity for transformation and growth. The authors suggest that organisations establish a supportive environment that includes a culture of trust and transparency for managers and offer them training in data literacy and ethical awareness. Furthermore, organisations should adopt a balanced approach that values technological advancement, ethical safeguards and human-centred practices to leverage the full potential of algorithmic management.
Keywords: Algorithmic management; Qualitative study; Retail industry; Technology acceptance model; Turkey